2008
DOI: 10.1002/pon.1425
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Distress Barometer’: validation of method of combining the Distress Thermometer with a rated complaint scale

Abstract: These results indicate that the Distress Barometer, which is convenient for both patients and doctors, can be used as an acceptable, brief and sufficiently accurate method for detecting distress in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 46 publications
5
38
1
6
Order By: Relevance
“…While the dichotomous problem list can provide additional information as to sources of distress and suggest referral needs, ''Yes'' or ''No'' answers are less likely to yield clinically useful information regarding response to an intervention and may not adequately represent the patient's total response to a specific problem area or the weight that problem carries for them in terms of distress. In order to address this issue, Akizuki et al added an Impact Thermometer to the DT to increase specificity and evaluate impairment of social functioning [41], and researchers in Belgium combined the DT with the colored complaint scale to create the ''Distress Barometer'' with the goal of improving the specificity of distress screening without decreasing the sensitivity of the DT [42].…”
Section: Discussionmentioning
confidence: 99%
“…While the dichotomous problem list can provide additional information as to sources of distress and suggest referral needs, ''Yes'' or ''No'' answers are less likely to yield clinically useful information regarding response to an intervention and may not adequately represent the patient's total response to a specific problem area or the weight that problem carries for them in terms of distress. In order to address this issue, Akizuki et al added an Impact Thermometer to the DT to increase specificity and evaluate impairment of social functioning [41], and researchers in Belgium combined the DT with the colored complaint scale to create the ''Distress Barometer'' with the goal of improving the specificity of distress screening without decreasing the sensitivity of the DT [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the SEPO study, Gil et al [34] found that a Mood Thermometer (MT) worked better than the DT in identifying patients with depression, suggesting that adding a specific 'mood' dimension could improve assessment in oncology clinics. A modification of the DT was proposed by Bauwens et al [35] who developed the Distress Barometer (DB) as a tool combining the DT and a Coloured Complaint Scale, aimed at improving the specificity of distress screening without decreasing the sensitivity of the DT and favouring the interpretation "at a single glance" of the nature and the intensity of distress in ambulatory cancer patients. More recently, Mitchell et al [36,37], developed a five-dimensional tool, the Emotion Thermometers (ET), as a combination of five Visual-Analogue Scales (VAS) in the form of four predictor domains (distress, anxiety, depression, anger) and one outcome domain (need for help).…”
Section: Clinical Limitations and Educational Needsmentioning
confidence: 99%
“…• "Escala coloreada" (Colored Complaint Scale, CCS) (26) . Identifica y cuantifica las fuentes de estrés percibido a través de 9 ítems que se responden según una escala coloreada con 5 opciones de respuesta (0, "ninguna molestia" y 4, "mucha molestia".…”
Section: Instrumentosunclassified
“…Además, el DT mostró la correlación más alta con los problemas de origen emocional y se asoció con cada uno de los problemas emocionales concretos evaluados: "nerviosismo/ansiedad", "tristeza" y, en menor grado, "ira". Así y contrariamente a los resultados obtenidos por otros autores (26) , nuestros datos respaldan la validez del DT en cuanto medida del rango de respuestas emocionales que engloba el término distrés.…”
Section: Discusión / Conclusionesunclassified
See 1 more Smart Citation